Species-Site Matching and Growth Prediction of Three Forest Plantation Species at Tawau, Sabah, Malaysia - Nathan, Ram (2009)
Sabah Softwoods Berhad venture into forest plantation was initiated in 1974. The trees species introduced were promising, but differences in yield and growth rate within its area continually repeated. Often, the yields were not within the expectation even when their genetic differences were narrowed down silviculturaly. To overcome such problems, study on species-site matching of Gmelina arborea, Paraserianthes falcataria and Acacia mangium were carried out with the aim of minimizing the variability in growth, thus maximizing yield. The effect of soil series (Paliu, Kumansi, Tanjong Lipat and Kapilit) and climate on tree species growth variables was a priority in the species-site matching and site suitability study. Correlation and regression analysis of growth with climate, site assessment with respect to tree species height growth (site index), formulation of growth and yield equation of each tree species, and the financial analysis to determine the prospect of species-site matching operations prior to forest tree plantation establishment were done in answering the growth variability, in improving silviculture and management of forest plantation, in ensuring future sustainability of its resources, and to secure its forest ecosystem in perpetuity The results revealed that temperature, relative humidity, rainfall, sunshine hours, wind run, degree of wetness, rain index, humidity coefficient, and dryness index coefficient of variations were less than 25%. Such findings related that the climate was not extreme. The analysis of soil series data revealed significant differences for the percentages of sand, clay, porosity, moisture content, and cation-exchange capacity. Paliu series was best for Gmelina arborea (22.52 m3ha-1yr-1) and Paraserianthes falcataria (34.18 m3ha-1yr-1). This soil series was very sandy and porous with moderate cation exchange capacity and moisture content. Acacia mangium growth showed no differences between the soil series. It grew equally well on any of the soil series in the area and its mean annual increment ranged between 19.06 m3ha-1yr-1 and 26.42 m3ha-1yr-1. The yields of tree species on their preferred soils were also highly correlated with daily sunshine hours. The climatic variables daily sunshine hours, temperature, rainfall, and raindays explained about 65 to 76% of the variations in their yields (m3ha-1) depending on tree species. The site assessment and classification based on site index equation derived for each tree species revealed that Gmelina arborea was site-specific species and grew best only in areas with site index class I. Gmelina arborea and Paraserianthes falcataria showed wider differences in height between its site index classes when compared with Acacia mangium as the former trees species varied significantly in growth rate between the soil series. Growth and and yield equations using height of dominant tree and diameter at breast height were derived for Gmelina arborea (R2 = 0.8947), Paraserianthes falcataria (R2 = 0.8961) and Acacia mangium (R2 = 0.7915).Financial analysis revealed carrying out of species-site matching operation prior to forest trees plantation is financially profitable (IRR = 22.09%). The Net Present Value remains positive and Benefit / Cost ratio is more than 1 at 10% and 15% discounted rate. Conclusively, the results of this study provided tools for species-site matching, forecasting growth, decision making, and planning of future planting of Acacia mangium, Gmelina arborea, and Paraserianthes falcataria.